The relative utilization of criminal sanctions in Canada: toward a comprehensive description of sentencing outcomes - Reid, Andrew A. (Canadian journal of criminology and criminal justice, 2017)
Canada's national statistics agency relies solely on counts, percentages, and measures of central tendency to report on sentencing outcomes in the country. While these techniques are familiar, simple to calculate, and easy to interpret, they each offer just one perspective. Consequently, important information may go unreported. This article proposes an alternative statistical approach - a relative utilization quotient - to offer an additional perspective. The technique is employed to calculate the extent to which criminal sanctions are used for a particular offence category, relative to their general use across all offence categories. Data from the adult component of the Integrated Criminal Court Survey (2013-14) are used to operationalize the technique in analyses covering five key categories of offences and a subset of detailed offence groupings. Results demonstrate that the relative utilization quotient reveals important patterns of sanction use and, when it is considered alongside conventional measurement strategies, a more complete understanding of sentencing outcomes may be obtained. Because of its valuable contribution and ease of calculation, it is argued that the strategy should be more widely adopted in studies of sentencing and criminal case processing.